Internationalisation of Higher Education in the Conditions of Globalization - Bulajeva, Tatjana (Acta Paedagogica Vilnensia, 2005)
The growing impact of globalisation is felt in different spheres of life. Internationalisation is one of the terms used to describe this impact, it is a phenomenon closely related to globalisation processes. Higher education sector seems to be most affected by both, because following the Bologna Declaration there should be a coherent and cohesive European Higher Education Area created by the year 2010. That is why it is important to explore the relationship between globalisation and internationalisation and analyse the international dimension of the higher education. Globalisation and internationalisation are seen as different but dynamically linked concepts: the first one is seen as catalyst, while the second one as the response. Internationalisation of higher education is one of the ways the country responds to the impact of globalisation. There are different approaches to internationalisation at institutional level as well as factors influencing its implementation. There are political, economic, academic, social and cultural rationales for wanting to integrate an international dimension into higher educational institutions. This is done undertaking different initiatives. In the process oriented approach to internationalisation, emphasis is put on the concept of sustaining the international and intercultural dimensions of research, teaching and services. The strategies used by institutions for that purpose focus on academic activities and organisational factors. The programme strategies refer to the initiatives which are academic in nature and are related to teaching, learning, training, research, advising and supporting international activities of institution. The organisational strategies help to ensure that international dimension is institutionalised through the development of appropriate human resources, policies, governance and administrative systems.